Syntaxin-1 is necessary for UNC5A-C/Netrin-1-dependent macropinocytosis and chemorepulsion - Martínez-Mármol, Ramón; Muhaisen, Ashraf; Cotrufo, Tiziana; Roselló-Busquets, Cristina; Ros, Oriol; Hernaiz-Llorens, Marc; Pérez-Branguli, Francesc; Andrés, Rosa Maria; Parcerisas, Antoni; Pascual, Marta; Ulloa, Fausto; Soriano, Eduardo (Frontiers in Molecular Neuroscience, 2023)
Introduction Brain connectivity requires correct axonal guidance to drive axons to their appropriate targets. This process is orchestrated by guidance cues that exert attraction or repulsion to developing axons. However, the intricacies of the cellular machinery responsible for the correct response of growth cones are just being unveiled. Netrin-1 is a bifunctional molecule involved in axon pathfinding and cell migration that induces repulsion during postnatal cerebellar development. This process is mediated by UNC5 homolog receptors located on external granule layer (EGL) tracts. Methods Biochemical, imaging and cell biology techniques, as well as syntaxin-1A/B (Stx1A/B) knock-out mice were used in primary cultures and brain explants. Results and discussion Here, we demonstrate that this response is characterized by enhanced membrane internalization through macropinocytosis, but not clathrin-mediated endocytosis. We show that UNC5A, UNC5B, and UNC5C receptors form a protein complex with the t-SNARE syntaxin-1. By combining botulinum neurotoxins, an shRNA knock-down strategy and Stx1 knock-out mice, we demonstrate that this SNARE protein is required for Netrin1-induced macropinocytosis and chemorepulsion, suggesting that Stx1 is crucial in regulating Netrin-1-mediated axonal guidance.